Radiative forcing from the 1991 Mount Pinatubo volcanic eruption - Stenchikov, G; Kirchner, I; Robock, A; Graf, H; Antuna, J; Grainger, R; Lambert, A; Thomason, L (Blackwell Publishing Ltd, 1998)
Volcanic sulfate aerosols in the stratosphere produce significant long-term solar and infrared radiative perturbations in the Earth's atmosphere and at the surface, which cause a response of the climate system. Here we study the fundamental process of the development of this volcanic radiative forcing, focusing on the eruption of Mount Pinatubo in the Philippines on June 15, 1991. We develop a spectral-, space-, and time-dependent set of aerosol parameters for 2 years after the Pinatubo eruption using a combination of SAGE II aerosol extinctions and UARS-retrieved effective radii, supported by SAM II, AVHRR, lidar and balloon observations. Using these data, we calculate the aerosol radiative forcing with the ECHAM4 general circulation model (GCM) for cases with climatological and observed sea surface temperature (SST), as well as with and without climate response. We find that the aerosol radiative forcing is not sensitive to the climate variations caused by SST or the atmospheric response to the aerosols, except in regions with varying dense cloudiness. The solar forcing in the near infrared contributes substantially to the total stratospheric heating. A complete formulation of radiative forcing should include not only changes of net fluxes at the tropopause but also the vertical distribution of atmospheric heating rates and the change of downward thermal and net solar radiative fluxes at the surface. These forcing and aerosol data are available for GCM experiments with any spatial and spectral resolution. Copyright 1998 by the American Geophysical Union.